HUBUNGAN SELF DIRECTED LEARNING READINESS DENGAN PRESTASI BELAJAR MAHASISWA TAHUN PERTAMA PROGRAM STUDI PENDIDIKAN DOKTER FKIK UNTAD - Kiay Demak, Indah Puspasari; Pasambo, Trisnawanta Asih (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2016)
Background. Self Directed Learning Readiness concept that requires students to be ready to plan, implement, and evaluate their own learning process can be used as a benchmark to measure the success of students in academic achievement in the learning environment.Purpose. The research was conducted to analyze the relationship of SDLR with academic achievement and pattern of SDLR for the first year student in Medical School of Tadulako University.Method. This research was an analytic study with cross-sectional approach. Subjects were 111 first year students. The score of SDLR was measured by a questionnaire. The correlation between the SDLR and academic achievement were analyzed by Spearman correlation test.Results. There were 68.5% students with high SDLR level and 31.5% students with medium SDLR level. The results of spearman test were 0.013 for p value and strength of correlation (r) 0.235.Conclusion. There is a significant correlation between SDLR and academic achievement of the first year medical student. However, this relationship is weak because of the multitude of factors that may affect the academic achievement of the students.Â Keywords: self-directed learning, readiness, academic achievement